Performance Assessment of Machine Learning Algorithms with Feature Selection Methods - Thakur, A (International Journal of Computer Sciences and Engineering, 2025)
Machine learning is a field of artificial intelligence in which computers learn from experience. The field of machine learning is a famous research area in computer science. Machine learning applications are helpful in various domains of computer science, chemical sciences, spatial technology, bioinformatics, agriculture, digital forensics and more. Machine learning algorithms are useful in the fields of pattern recognition, pattern classification, text classification, SMS classification, computer vision, mobile learning and more. In the present work performance assessment of three machine learning algorithms namely logistic regression, random forest and naïve bayes with three feature selection methods viz. correlation based, Information based and gain ratio is conducted on a mobile device. The above-mentioned machine learning algorithms along with feature selection methods are assessed for the performance metrics of accuracy, precision, F- Measure, recall and Receiver Operating Characteristics.